Efficacy of topical 0.5% bupivacaine in pain reduction in pediatric tonsillectomy patients - Sabih Nadeem Qamar; Zia us salam qazi; Sarfraz Latif; Sadia Maqsood Awan; Saulat Sarfraz; Riffat Saeed (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Palatine tonsils are lymphoid organs in the oropharynx part of the waldeyer's ring and serve as host defence organs with maximum immunological activity from 3-10 years. Tonsillectomy is associated with considerable postoperative pain and requires significant consumption of analgesia. This study aimed to determine effect of topically suffused 0.5% bupivacaine on postoperative tonsillectomy pain.RESULTS One hundred & twenty (120) patients with 61 males and 60-patients in each group with age range of 5-15 years (Group-A=8.63±2.63 and Group-B=8.32±6.60 in). Mean BMI of Group-A and group-B was 15.18±1.60 and 14.96±1.34 respectively (p=0.417). Mean pain score in group-A and group-B was 2.63±0.938 and 6.07±0.800 respectively (p<0.001).CONCLUSION: nsillectomies performed using bupivacaine-soaked packs postoperatively are associated with lower postoperative pain compared with those packed with normal saline.